The Characterization of Vegetable Tannins and Colouring Agents in Ancient Egyptian Leather from the Collection of the Metropolitan Museum of Art. (28th April 2016) - Elnaggar, A.; Leona, M.; Nevin, A.; Heywood, A.
Abstract : This work characterizes both tanning and colouring materials found in ancient Egyptian leather objects from the Metropolitan Museum of Art. The analytical investigations focused on assessing the development of the technology of ancient tanners using high‐performance liquid chromatography (HPLC), surface‐enhanced Raman spectroscopy (SERS), X‐ray fluorescence (XRF), Fourier transform infrared spectroscopy (FT–IR), X‐ray radiography and a scanning electron microscope connected to an energy‐dispersive X‐ray detector (SEM–EDX). Reference leather samples and archaeological leather objects were investigated to identify the animal skin species and the early use of hydrolyzable vegetable tannins for leather tanning. Different methods were used to colour th leather, including madder dying and staining with hematite, or painting with Egyptian blue and Egyptian green.